2018
DOI: 10.1016/j.cardfail.2018.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cardiac Troponin I Levels Measured by a Novel Highly Sensitive Assay in Acute Decompensated Heart Failure: Insights From the ASCEND-HF Trial

Abstract: Circulating cTnI level was associated with clinical outcomes in ADHF, but these observations diminished with additional adjustment for NT-proBNP. Although they likely represent a spectrum of risk in ADHF, these findings question the implications of changing cTnI levels during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
(45 reference statements)
0
5
1
Order By: Relevance
“…Unlike prior HF clinical trials, where myocardial injury with higher sensitivity assays above the MI threshold exceeds 90%, 18,26 the proportion of patients with myocardial injury was much lower in our cohort; 66% to 77% depending on the threshold. Despite a smaller proportion of myocardial injury patients, 30-day outcomes were similar.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Unlike prior HF clinical trials, where myocardial injury with higher sensitivity assays above the MI threshold exceeds 90%, 18,26 the proportion of patients with myocardial injury was much lower in our cohort; 66% to 77% depending on the threshold. Despite a smaller proportion of myocardial injury patients, 30-day outcomes were similar.…”
Section: Discussioncontrasting
confidence: 67%
“…19,27 The preponderance of evidence supports troponin as an adverse prognostic marker; however, not all studies have found troponin to be a risk factor for mortality. 26,28 In the era of newer, more highly sensitive assays, how to best interpret an elevated troponin is also not well known. While we utilized the value the 4 th Universal Definition of Myocardial Infarction 29 as the diagnostic threshold for myocardial injury in the setting of suspected ACS, these are unlikely to be the ideal cut-points for risk in AHF.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies showing that cTnI was induced in patients with FM and those with AMI‐induced acute HF, compared with patients with other causes induced by hemodynamically unstable acute HF. 35 , 36 Therefore, the plasma sST2 induction observed in patients with FM may not only be caused by a generic systemic inflammatory response but also by local cardiac stress. From longitudinal examination, we further demonstrated that the induction of plasma sST2 was observed at the onset of FM, then dynamically normalized along with the resolution of the disease during hospitalization and remained stable during post‐FM period.…”
Section: Discussionmentioning
confidence: 99%
“… 33 In a multi‐marker strategy, patients with all three biomarkers below their optimal cutoff point (based upon the receiver operating characteristic curves) had the best survival (0% death) at a median follow‐up of 739 days, while 53% of those with elevation of all three biomarkers died. Concentrations of cardiac troponin may also be useful to predict in‐hospital 20 , 34 and post‐discharge outcomes following hospital‐based treatment for acute HF. 35 , 36 For example, in one cohort of 1074 patients with acute HF undergoing serial measurement of hs‐cTnT, higher baseline or peak hs‐cTnT and greater peak change predicted adverse outcome, particularly strongest for 180‐day cardiovascular mortality (HR per doubling of baseline hs‐cTnT 1.36; 95% CI 1.15–1.60).…”
Section: Cardiac Specificmentioning
confidence: 99%